2000
DOI: 10.1089/10949310050078869
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Brain Activity During Use of Stereoscopic Virtual Environments

Abstract: Performance in virtual environments (VEs) is strongly modulated by attention-related factorssuch as the preattentive state of the brain. Because this state changes over time and might also be influenced by the VE, itself, we propose an implementation of an electrophysiological brain monitoring system focussing on event-related potentials (ERPs) and conventional EEG signals. ERPs provide information related to the respective cognitive functional state as a reliable method for assessing the underlying brain acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Because integration of a virtual reality (VR) component into ERP research is a relatively novel approach, concerns that the use of this technology may be related to the aberrant findings warrant consideration. Although research on the effects of virtual environments (VE) is scant (Mager, Bullinger, Mueller-Spahn, Kuntze, & Stoermer, 2001;Mager, Bullinger, Roessler, Mueller-Spahn, & Stoermer, 2000), data suggest that ERPs in response to VE are not different from ERPs in naturalistic settings. Moreover, the present study utilized a mixed design, with the VE only being used to encode a minority of probe items; most probes were learned via a standard reading task.…”
Section: Deception Detections and Erps 293mentioning
confidence: 99%
“…Because integration of a virtual reality (VR) component into ERP research is a relatively novel approach, concerns that the use of this technology may be related to the aberrant findings warrant consideration. Although research on the effects of virtual environments (VE) is scant (Mager, Bullinger, Mueller-Spahn, Kuntze, & Stoermer, 2001;Mager, Bullinger, Roessler, Mueller-Spahn, & Stoermer, 2000), data suggest that ERPs in response to VE are not different from ERPs in naturalistic settings. Moreover, the present study utilized a mixed design, with the VE only being used to encode a minority of probe items; most probes were learned via a standard reading task.…”
Section: Deception Detections and Erps 293mentioning
confidence: 99%
“…9 A few researchers, therefore, have tried to objectively measure anxiety and stress responses in real time by using physiological response such as heart rate, respiration rate, skin resistance, skin temperature, and peripheral brain wave EEG activity in virtual environments. [10][11][12][13] Wiederhold et al found differences between the phobic's physiological responses and nonphobics' responses when placed in a virtual flying environment related to their phobia. 10 Meehan found a high and significant correlation between presence and skin conductance level with 10 nonphobic participants in virtual room environments.…”
Section: Introductionmentioning
confidence: 99%
“…10 Meehan found a high and significant correlation between presence and skin conductance level with 10 nonphobic participants in virtual room environments. 11 Stoermer et al showed heart rate variability was a powerful and easy-to-use instrument for monitoring the user's stress level. 12 While these studies all showed the necessity of monitoring user's psychophysiological states in VR psychotherapy, they did not find a systematic relationship between nonphobics' and phobics' physiological response to virtual environments.…”
Section: Introductionmentioning
confidence: 99%
“…A number of physiological measures have been used to assess emotional reaction and engagement, two constructs which are vital parts of psychological validity. Heart rate (Meehan et al, 2002) and galvanic skin response (Wiederhold & Wiederhold, 2000;Meehan et al, 2002;Jang et al, 2002) have both been shown to be good correlates with engagement or emotional arousal, as has electroencephalography (Mager et al, 2000;Pugnetti, Meehan, and Mendozzi, 2001).…”
Section: Categories Of Fidelitymentioning
confidence: 99%